Introduction - Schirmer, Elizabeth (The Yearbook of Langland Studies, 2024)
Abstract Reads Piers Plowman as a series of experiments in ‘extramural pedagogy’ that, as such, provides fertile ground for rethinking the work of literary pedagogy both in Langland’s time and in our own. Despite its difficulties, as the essays collected here show, Piers as a teaching text at all levels of the curriculum can invite students to think through their own experience of conflict and injustice — and their own educational journeys — in conversation with the past. At the same time, these essays draw on the experience of teaching to intervene critically in the field of Langland studies, challenging any easy distinction between research as the creation of knowledge and teaching as its transmission. This Introduction establishes the Langland classroom as a place where academic expertise meets lived experience, and both emerge changed from the encounter.
Keywords: medieval literary studies